Blocking the VISTA pathway enhances disease progression in (NZB × NZW) F1 female mice. (February 2018) - Sergent, PA; Plummer, SF; Pettus, J; Mabaera, R; DeLong, JK; Pechenick, DA; Burns, CM; Noelle, RJ; Ceeraz, S
V-domain Ig suppressor of T-cell activation (VISTA) is a critical negative checkpoint molecule involved in regulating the immune response. Targeting the pathway with an antagonist anti-VISTA antibody designated 13F3 has been shown to enhance disease severity in experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis. To determine if VISTA plays a role in murine lupus, New Zealand Black × New Zealand White (BWF1 ) mice were treated with 13F3 or control hamster Ig and disease monitored. Onset of proteinuria was earlier and renal damage more profound in mice treated with 13F3. Cell subset analysis showed an increase of activated splenic T cells and inflammatory splenic myeloid cells, but no effect on B cells, in mice receiving 13F3. Examination of the kidney showed an increase in inflammatory myeloid cell infiltration with 13F3 treatment. This study along with previous EAE data, suggests that interventions that enhance VISTA regulatory activity may be effective for the treatment of autoimmune disease.